Genome-Wide Identification and Gene Expression Analysis of Acyl-Activating Enzymes Superfamily in Tomato (Solanum lycopersicum) Under Aluminum Stress - Jin, Jian Feng; He, Qi Yu; Li, Peng Fei; Lou, He Qiang; Chen, Wei Wei; Yang, Jian Li (Frontiers in Plant Science, 2021)
In response to changing environments, plants regulate gene expression and subsequent metabolism to acclimate and survive. A superfamily of acyl-activating enzymes (AAEs) have been observed in every class of creatures on planet. Some of plant AAE genes have been identified and functionally characterized to be involved in growth, development, biotic and abiotic stresses via mediating diverse metabolic pathways. Nevertheless, little information is available about AAEs superfamily in tomato (Solanum lycopersicum), the highest-value fruit and vegetable crop globally. In this study, we aims to identify tomato AAEs superfamily and investigate potential functions with respect to aluminum (Al) stress that represents one of the major factors limiting crop productivity on acid soils worldwide. Fifty-three tomato AAE genes were identified and named on the basis of phylogenetic relationships between Arabidopsis and tomato. Phylogenetic analysis showed that AAEs could be classed into 6 clades; however, clade III contains no tomato AAE genes. Synteny analyses revealed tomato veritable paralogs and Arabidopsis orthologs. RNA-seq and qRT-PCR analysis indicated that 9 out of 53 AAEs genes were significantly up- or down-regulated by Al stress. Numerous cis-acting elements implicated in biotic and abiotic stresses were detected in the promoter regions of SlAAEs. As the most abundantly expressed gene in root apex and highly induced by Al, there are many potential STOP1 cis-acting elements present in the promoter of SlAAE3-1, and its expression in root apex was specific to Al. Finally, transgenic tobacco lines overexpressing SlAAE3-1 displayed increased tolerance to Al. Altogether, our results pave the way for further studies on functional characterization of SlAAE genes in tomato with an wish of tomato crop improvement in the future.